求导y=2x^3-3x+(√x)-1/x√x
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 00:22:47
求导y=2x^3-3x+(√x)-1/x√x求导y=2x^3-3x+(√x)-1/x√x求导y=2x^3-3x+(√x)-1/x√xy''=6x^2-3+1/(2√x)+3/2*x^(-5/2)
求导y=2x^3-3x+(√x)-1/x√x
求导y=2x^3-3x+(√x)-1/x√x
求导y=2x^3-3x+(√x)-1/x√x
y'=6x^2-3+1/(2√x)+3/2*x^(-5/2)
求导y=2x^3-3x+(√x)-1/x√x
y=(x^2-3x+3)/√x求导.
y=3^-x*x^2,求导
y=x/(x^2+3)求导
y=(3x^2-x√x+5√x-9)/√x 求导
用对数求导法求导:y=[x*(x^2+1)/(x-1)^2]^1/3
求导:Y=(x-1)(x-2)(x-3)…(x-2005) (x>2005)
y=log10(x^3+2x^2+x) 求导
y=3^x*e^x-2^x+e求导
Y=√(2X+4)-√(X+3) 求导
求导y=(2x^2-1)(3x+1)
y=(2x+1)(3x+2)函数求导
y=(x^2 +3)*e^(x^2 +1)求导.
求导 y=3x/(1+x^2)
y=x²/(2x+1)^3 求导
求导Y=X-1/√X
求导.y=x ln^3x
y=2^x+1/x求导